Peran Kiai dalam Membina Akhlakul Karimah Santri (Studi Kasus di Pondok Pesantren Aqidah Usymuni Terate Pandian Sumenep) - Aisyah, Siti; Kamal, Moh. Zainol (LP3M Universitas Al-Qolam Malang, 2023)
Kiai is a central figure in every Islamic boarding school. Kiai not only because of their knowledge, but also because they are the founders, owners and endowments of the Islamic boarding school itself. Their struggles and sacrifices are not limited to knowledge, energy and time, but also land and other materials given for the advancement of the spread of Islam. This research aims to describe the role of kiai at the Aqidah Usymuni Islamic boarding school in developing the morals of students and the inhibiting and supporting factors in carrying out their role. This research uses a qualitative approach with a case study type of research and uses observation, interview and documentation methods as data collection techniques. The informant is a kiai who is a caretaker at the Aqidah Symuni Islamic boarding school in Sumenep. The results of this research show several roles carried out by kiai including Kiai as caregivers, Kiai as teachers, Kiai as parents for students. Keywords : Kiai Roles, Akhlaqul Karimah